2015
DOI: 10.1063/1.4939096
|View full text |Cite
|
Sign up to set email alerts
|

Photon-assisted tunneling through a topological superconductor with Majorana bound states

Abstract: Employing the Keldysh Nonequilibrium Green’s function method, we investigate time-dependent transport through a topological superconductor with Majorana bound states in the presence of a high frequency microwave field. It is found that Majorana bound states driven by photon-assisted tunneling can absorb(emit) photons and the resulting photon-assisted tunneling side band peaks can split the Majorana bound state that then appears at non-zero bias. This splitting breaks from the current opinion that Majorana boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…where c † kα (c kα ) creates (annihilates) an electron of momentum k, energy ε kα in the lead α = L, R. For the QD, [21]. Here, we have assumed that the photon field with strength d and frequency ω p is applied only on the QD and the leads are free from its irradiation, and then only the dot's energy level is time-varying.…”
Section: Model and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…where c † kα (c kα ) creates (annihilates) an electron of momentum k, energy ε kα in the lead α = L, R. For the QD, [21]. Here, we have assumed that the photon field with strength d and frequency ω p is applied only on the QD and the leads are free from its irradiation, and then only the dot's energy level is time-varying.…”
Section: Model and Methodsmentioning
confidence: 99%
“…A vast of experimental works have been devoted to the detection of MBSs, relying on the signatures probably induced by the MBSs, including the 4π periodic Josephson current-phase in junctions between topological superconductors [13], half-integer conductance plateau at the coercive field in a hybrid structure composing of topological superconductors and topological quantum anomalous Hall insulator [6], tunneling spectroscopy using the Rashba nanowires coupled to the bulk s-wave superconductors [10], zero-bias of the differential conductance at the edges of the wires [14,15], the non-locality [16][17][18][19] and Kondo effect [20] influenced by MBSs. Since the above signatures can also be brought about by other mechanisms, some alternative schemes then have been continually put forward, such as the optical detection ones [21][22][23]. In [21], the authors found that the MBSs will absorb(emit) photons and result in photon-assisted tunneling side band peaks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Some other recent researches concerning topological superconductor include. 14,15 But, so far, it has been largely overlooked for the 2D TR breaking C 2 = −1 (class C in the Altland-Zirnbauer(AZ) classification 16,17 ) topological superconductors and for the 3D TR invariant class CI topological superconductors with T 2 = 1 and C 2 = −1. A few previous researches, by constructing theoretical models for simplest cases, include.…”
Section: Introductionmentioning
confidence: 99%